Analysis of Lipid-linked Oligosaccharides Synthesized in vivo in Schizosaccharomyces pombe - Valko, Ayelén (2022)
Dolichol diphosphate-linked oligosaccharides (LLO) are the sugar donors in N-glycosylation, a fundamental protein post-translational modification of the eukaryotic secretory pathway. Defects in LLO biosynthesis produce human Congenital Disorders of Glycosylation Type I. The synthesis of LLOs and the transfer reactions to their protein acceptors is highly conserved among animal, plant, and fungi kingdoms, making the fission yeast Schizosaccharomyces pombe a suitable model to study these processes. Here, we present a protocol to determine the LLO patterns produced in vivo by S. pombe cells that may be easily adapted to other cell types. First, exponentially growing cultures are labeled with a pulse of [14C]-glucose. LLOs are then purified by successive extractions with organic solvents, and glycans are separated from the lipid moieties in mild acid hydrolysis and a new solvent extraction. The purified glycans are then run on paper chromatography. We use a deconvolution process to adjust the profile obtained to the minimal number of Gaussian functions needed to fit the data and determine the proportion of each species with respect to total glycan species present in the cell. The method we provide here might be used without any expensive or specialized equipment. The deconvolution process described here might also be useful to analyze species in non-completely resolved chromatograms.